Changes in Ultrasonographic Vascularity Upon Initiation of Adalimumab Combination Therapy in Rheumatoid Arthritis Patients With an Inadequate Response to Methotrexate. Issue 11 (29th September 2016) - Kaeley, Gurjit S.; Nishio, Midori J.; Goyal, Janak R.; MacCarter, Daryl K.; Wells, Alvin F.; Chen, Su; Kupper, Hartmut; Kalabic, Jasmina
Abstract : Objective: To assess joint disease activity by ultrasound (US) in patients with rheumatoid arthritis (RA) initiating treatment with adalimumab (ADA) plus methotrexate (MTX). Methods: Data for this post hoc analysis originated from the MUSICA trial (ClinicalTrials.gov identifier: NCT01185288), which evaluated the efficacy of initiating ADA (40 mg every other week) plus 7.5 or 20 mg/week MTX in 309 patients with RA with an inadequate response to MTX. Synovial vascularization over 24 weeks was assessed bilaterally at metacarpophalangeal joint 2 (MCP2), MCP3, MCP5, metatarsophalangeal joint 5, and the wrists by power Doppler US (PDUS). A semiquantitative 4‐grade scale was used. Disease activity was assessed using the Disease Activity Score in 28 joints using the C‐reactive protein level (DAS28‐CRP) and Simplified Disease Activity Index (SDAI). The correlation between continuous variables was assessed using Pearson's correlation coefficient. Results: After 24 weeks of treatment with ADA plus MTX, rapid improvements in the mean synovial vascularity score were observed; the greatest improvements were in MCP2 (−0.5), MCP3 (−0.4), and the wrist (−0.4). At week 24, patients with the lowest DAS28‐CRP (<2.6) had the lowest mean 5‐joint and 3‐joint composite synovial vascularity scores. The 5‐joint and 3‐joint scores were strongly correlated (ρ > 0.9). Synovial vascularity scores correlated poorly with DAS28, swollen joint count in 66 joints (SJC66), SJC28, tender joint count in 68 joints (TJC68), TJC28, Clinical Disease Activity Index (CDAI), SDAI, physician's global assessment, patient's global assessment of pain, and disease duration (ρ < 0.2). Thirty‐two (70%) of 46 patients with a DAS28‐CRP of <2.6, and 11 (58%) of 19 patients with an SDAI indicating remission had at least 1 joint with a synovial vascularity score of ≥1. Conclusion: PDUS detects changes in synovial vascularity in RA patients treated with ADA plus MTX, and residual synovial vascularity in patients in whom clinical disease control has been achieved.